Dinamika Spasial Perubahan Penggunaan Lahan dan Potensi Lahan Pertanian pada Daerah Aliran Sungai Tropis: Studi Kasus Sub Das Melawi, Indonesia - Rini Hazriani; Romiyanto Romiyanto; Fitriana Fitriana; Gunadi Gunadi (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2026)
Land-use change within watersheds represents a major challenge for land resource management, as it impacts agricultural productivity, hydrological functions, and environmental sustainability. The Melawi Sub-watershed, part of the Kapuas Watershed, is experiencing land-use dynamics driven by plantation expansion, agricultural activities, and shifts in spatial utilization. This study aims to analyze land-use change dynamics in the Melawi Sub-watershed from 2022 to 2024, evaluate the presence of agricultural land within forest areas and Business Use Rights (HGU) zones, and identify potential agricultural land available for future development. The analysis utilized Sentinel-2 imagery processed on the Google Earth Engine platform using the Random Forest algorithm; subsequent spatial overlay analysis generated a land-use change matrix and identified land distribution across forest areas and HGU zones. The results indicate an increase in plantation area by 20,153.357 hectares, while mixed dryland agriculture and shrubland decreased by 26,879.009 hectares, signaling a conversion toward more intensive land use. Overlay results reveal that of the total 1,148,066.594 hectares of agricultural land, approximately 540,005.663 hectares (47.04%) are located within forest areas, and 99,339.002 hectares (8.65%) fall within HGU zones. After accounting for these areas, a potential 508,721.929 hectares (44.31%) of agricultural land remains available for sustainable agricultural development. Key words: Land Use Change, Melawi Sub-watershed, Sentinel-2